Salicylic acid‐dependent immunity contributes to resistance against Rhizoctonia solani, a necrotrophic fungal agent of sheath blight, in rice and Brachypodium distachyon. Issue 2 (19th October 2017) - Kouzai, Yusuke; Kimura, Mamiko; Watanabe, Megumi; Kusunoki, Kazuki; Osaka, Daiki; Suzuki, Tomoko; Matsui, Hidenori; Yamamoto, Mikihiro; Ichinose, Yuki; Toyoda, Kazuhiro; Matsuura, Takakazu; Mori, Izumi C.; et al.
Summary: Rhizoctonia solani is a soil‐borne fungus causing sheath blight. In consistent with its necrotrophic life style, no rice cultivars fully resistant to R. solani are known, and agrochemical plant defense activators used for rice blast, which upregulate a phytohormonal salicylic acid (SA)‐dependent pathway, are ineffective towards this pathogen. As a result of the unavailability of genetics, the infection process of R. solani remains unclear. We used the model monocotyledonous plants Brachypodium distachyon and rice, and evaluated the effects of phytohormone‐induced resistance to R. solani by pharmacological, genetic and microscopic approaches to understand fungal pathogenicity. Pretreatment with SA, but not with plant defense activators used in agriculture, can unexpectedly induce sheath blight resistance in plants. SA treatment inhibits the advancement of R. solani to the point in the infection process in which fungal biomass shows remarkable expansion and specific infection machinery is developed. The involvement of SA in R. solani resistance is demonstrated by SA‐deficient NahG transgenic rice and the sheath blight‐resistant B. distachyon accessions, Bd3‐1 and Gaz‐4, which activate SA‐dependent signaling on inoculation. Our findings suggest a hemi‐biotrophic nature of R. solani, which can be targeted by SA‐dependent plant immunity. Furthermore, B. distachyon provides a genetic resource that can confer disease resistance against R. solani to plants.